The Evidence Chamber: Playful Science Communication and Research Through Digital Storytelling - Doran, Heather; Barnard, Dan; McAlister, Joe; Briscoe, Rachel; Hackman, Lucina; Nic Daeid, Niamh (Frontiers in Communication, 2021)
In a courtroom, it is essential that the scientific evidence is both understandable and understood, so that the strengths and limitations of that evidence, within the context of a case, can inform decision making. The Evidence Chamber brings together entertainment, public engagement with science and research in a public performance activity that is centred around digital storytelling and science communication. This experience engages public audiences with science and allows a better understanding of how people interpret scientific evidence. In this paper, we discuss how we created this experience as an in-person and fully virtual performance through successful collaboration between forensic science research, the public, public engagement, the legal profession, and digital performance artists.